A Titanium Dioxide Supported Gold Nanoparticle Catalyst for the Selective N‐Formylation of Functionalized Amines with Carbon Dioxide and Hydrogen. Issue 19 (21st August 2017) - Mitsudome, Takato; Urayama, Teppei; Fujita, Shu; Maeno, Zen; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda, Kiyotomi
Abstract: A TiO2 ‐supported, gold nanoparticle catalyst was found to allow the N‐formylation of various amines, including normally unreactive anilines, by using CO2 as the carbonyl source under a H2 atmosphere. A series of reducible functional groups, such as olefins, halogens, carbonyls, carbamates, and cyano moieties, were completely retained during the formylation, which proved the highly selective nature of the formylation reaction. The catalyst was also found to be reusable without any loss of activity or selectivity. Abstract : Feels like the first time : TiO2 ‐supported Au nanoparticles are, for the first time, shown to promote the selective N‐formylation of various amines to formamides in excellent yields without the hydrogenation of reducible functional groups. This catalyst system has significant advantages over homogeneous catalysts, including a simple workup procedure, high reusability, and applicability to a wide range of substrates.